Understanding the formation of powder bed cavities in paving by the van der Waals force - Lei Shi; Jing Xue; Pubao Li; Haijun Huang; Xiaojiang Xia (Journal of Materials Research and Technology, 2025)
Powder-bed-fusion (PBF) additive manufacturing of high-performance alloys (e.g. GH3536) necessitate stringent control of powder bed quality to mitigate defects, particularly cavities that compromise component integrity. By employing the Johnson-Kendall-Roberts (JKR) theoretical framework, this study investigates the role of van der Waals forces in cavity formation within GH3536 powder beds and their dependence on particle size distribution (PSD). The results demonstrate that van der Waals forces significantly contribute to cavity initiation: coarse particles offer preferred locations for particle detachment, whereas fine particles enhance packing stability. A novel parameter, the characteristic length is introduced to predict particle contact likelihood, with higher values indicating stronger interparticle adhesion. Void fraction exhibit inverse correlation with the prevalence of small particles in the feedstock, underscoring the importance of PSD optimization. These findings provide actionable guidance for engineering GH3536 powder feedstocks to restrain the cavities formation, thereby advancing PBF processes for critical applications. This work fills the fundamental knowledge gap between the interaction of particles and PSD related to the powder bed quality, constructing g a predictive framework for powder engineering in additive manufacturing.